Influence of NPK fertilizer rates and irrigation frequencies on the biomass and yield components of sweet corn (Zea mays L.) - Muhumed, Mohamed Abdulrahman; Jusop, Shamshuddin; Teh, Christopher Boon Sung; Megat Wahab, Puteri Edaroyati; Panhwar, Qurban Ali (WFL Publisher, 2014)
Application of adequate fertilizers becomes one of the most important agronomic practices to sustain corn production on soils of the tropical regions, which are mostly acidic and poor in nutrients. An experiment under rain shelter was conducted at the Faculty of Agriculture, Universiti Putra Malaysia, Serdang to evaluate the influence of different NPK fertilizer rates on the biomass and yield components of sweet corn. The experiment was carried out using split plot design with four replications. Three drip irrigation frequencies as a main plot: [Once in 2 days (Ir1), once in 3 days (Ir2) and once in 4 days irrigations (Ir3)] and four NPK fertilizer rates as sub-plot [0:0:0 (0%), 60:30:45 (50%), 120:60:90 (100%) and 180:90:135 (150%), henceforth referred to as F1, F2, F3 and F4, respectively] were tested in this experiment. The results of the study showed that total dry matter significantly (P<0.05) increased with increase in the irrigation frequencies. For Ir1 treatments at F4 fertilizer rate, the shoot dry weight was higher compared to the other fertilizer rates due to better nutrient supply to the plant. Similarly, irrigation frequency and fertilizer levels significantly (P<0.05) influenced the yield components. Ear, cob and grain were found to have higher weight for once in 2 days irrigation frequency with fertilizer level of F4. When fertilizer rate was increased from 100% (F3) to 150% (F4), ear, cob and grain weight were increased by 25%, 39% and 23%, respectively.